2013
DOI: 10.7314/apjcp.2013.14.5.2897
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based Case-control Study on Risk Factors for Gastric Cardia Cancer in Rural Areas of Linzhou

Abstract: Gastric cancer is the second most common cause of cancer-related deaths in the world. Although certain dietary factors and lifestyles have been suggested to be associated with gastric carcinogenesis, there have been few investigations focusing on rural areas. A case-control study was therefore carried out to investigate the risk factors of gastric cardia cancer (GCC) in rural areas of Linzhou. A total of 470 newly diagnosed cases of GCC and 470 healthy controls were included. Face-to-face interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
(29 reference statements)
1
26
0
Order By: Relevance
“…but in Sun`s study there was no significant relationship between irregular lunch-time and risk of gastric cardia cancer (Sun et al, 2013). It seems that irregular meal time leads to gastritis or gastro duodenal ulcers (Lim et al, 2013), if these predisposing factors presented for long time with no treatments, we could expect gastric cancer occurrence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…but in Sun`s study there was no significant relationship between irregular lunch-time and risk of gastric cardia cancer (Sun et al, 2013). It seems that irregular meal time leads to gastritis or gastro duodenal ulcers (Lim et al, 2013), if these predisposing factors presented for long time with no treatments, we could expect gastric cancer occurrence.…”
Section: Discussionmentioning
confidence: 92%
“…Along with other studies, results showed that specific eating behaviors (effective food chewing, eating slowly (speed of eating)), were identified as a preventive factor (Gao et al, 1999;Sierpinska et al, 2007;Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The essence of risk modeling is to obtain accurate relative and attributable risk estimates for etiologic factors, e.g., demographics, reproductive history, smoking, dietary patterns and medications (Sun et al, 2013). This depends on a clear understanding of the nature of all the individual factors involved and interactions between them.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a positive association between green tea consumption and UADT cancers; evidence indicates that it is caused by thermal injury resulting from consuming tea at high temperatures. [6][7][8][9][10][11][12][13] Further study is needed to validate this association between coffee consumption and UADT cancers and to determine if consumption of tea at lower temperatures would also confer a protective effect against UADT cancers.…”
Section: Epidemiologymentioning
confidence: 99%
“…Evidence indicates that the recurrent thermal injury to the mucosa that occurs with the consumption of heated beverages such as coffee, tea and mate causes upper aerodigestive tract (UADT) cancers. [6][7][8][9][10][11][12][13] In a report published jointly by the World Cancer Research Fund and the American Institute for Cancer Research, the panel concluded that although evidence was lacking, high-temperature drinks were a limited or suggestive cause of esophageal cancer. 14 Epidemiologic studies of the association between UADT and cancer and coffee consumption have been inconsistent, although a recent meta-analysis found that coffee consumption is inversely associated with cancer of the oropharynx and esophagus.…”
mentioning
confidence: 99%